Human tracking algorithm for video surveillance - Kamru Zaman, Fadhlan H.; Shafie, Amir Akramin; Khalifa, Othman Omran (IIUM Press, 2011)
Video surveillance is an important tool to enhance public safety and privacy protection. According to Hosik et al (2009), surveillance cameras as in CCTV systems for instance are widely deployed in strategic places such as airports, banks, and public transportation facilities, as well as in public places such as stores, elevators, and hallways. Hosik et al (2009) added that the surveillance cameras in London provided key photos of the men who bombed the underground system in July 2005 while the latest terrorist attack in London was foiled in 2007, partly thanks to the millions of surveillance cameras that London authorities have installed across the city. In order to fight crimes, video surveillance is also used in commercial locations such as banks, automated teller machines (ATMs), supermarkets, and parking areas to prevent and track criminal activities whereas consumer adoptions of video surveillance also have soared in recent years due to the increasing concern on privacy protection (Limin et aI, 2009).